PEMANFAATAN PENGGUNAAN MEDIA PEMBELAJARAN IPS DI SDN NURUL JIHAD DESA SERAPUH PADA MASA PANDEMIK - Dwi Pratiwi, Ajeng; Yulia Dalimunthe, Siska; Rahmadina, Idjah (Cv Arsy Persada Quality, 2022)
Media is a tool that can help the learning process. The use of learning media is considered to be able to help achieve the learning process. The use of learning media during a pandemic like this is much in demand, learning media which are included as learning resources other than teachers are considered to be able to answer challenges and problems that often occur in the learning process, including social studies learning that uses learning media as a tool of the learning process itself. The use of learning media is also expected to be able to improve student learning outcomes and achievement and students' understanding of social studies learning.